Growth co-movements between Nigeria and its industrialized trade partners: Does the decoupling hypothesis hold for Nigeria? - Adesola Ibironke (West African Journal of Monetary and Economic Integration, 2017)
Are there still significant common macroeconomic fluctuations between Nigeria and its industrial trade partners, even with the increased growth performance and resilience of emerging market and developing economies to developments originating from advanced economies in recent years? This paper answers this question by empirically exploring oil-related growth fluctuations between Nigeria and its two main (industrial) trade partners, namely the US and the Euro Area. This involves testing for Nigeria a relatively new hypothesis in the literature dealing with the subject in question, namely the decoupling hypothesis. The main finding is that the decoupling hypothesis does not hold for Nigeria, as there is a statistically significant degree of growth fluctuations between the country and its two industrial trade partners. Key policy implications of this finding are: (i) Trade links between Nigeria and its industrial counterparts constitute a significant source of macroeconomic risk for the former, as fluctuations imply uncertainty and risk. (ii) Apart from adopting shock-absorbing macroeconomic policies, diversifying trade away from industrial trade partners and increasing regional trade such as trade within the West African Monetary Zone (WAMZ), may be an effective policy through which Nigeria can limit vulnerability to fluctuations originating from industrial trade partners
Keywords: F15; F4; F41; O19; O55; 330; Economic Integration; Macroeconomic Aspects of International Trade and Finance; Open Economy Macroeconomics; International Linkages to Development; Africa